Photocatalytic degradation of recalcitrant aromatic hydrocarbon compounds in oilfield-produced water: A critical review - Ojo Samuel, Ojo Samuel; Othman, Mohd Hafiz Dzarfan; Kamaludin, Roziana; Dzinun, Hazlini; Imtiaz, Aniqa; Tao Li, Tao Li; Tijjani El-badawy, Tijjani El-badawy; Asmat Ullah Khan, Asmat Ullah Khan; Puteh, Mohd Hafiz; Erna Yuliwati, Erna Yuliwati; Tonni Agustiono Kurniawan, Tonni Agustiono Kurniawan (Elsevier, 2023)
Oilfield-produced water (OPW) contains a complex mixture of toxic and hazardous organic and inorganic compounds. Refractory polycyclic aromatic hydrocarbons (PAHs) and polyaromatic hydrocarbons such as benzene, toluene, ethylbenzene, and xylene (BTEX) chemical compounds present in OPW which result from hydrocarbon sources and chemicals added during the oil recovery process, have become a source of global concern. Their continuous presence in the OPW requires suitable technology to remove them before their discharge to the environment. When the OPW contains harmful pollutants combined with oil in minute size, the treatment performance of various water technologies appears insufficient due to the generation of secondary by-products, which are also recalcitrant and toxic. To consolidate scattered knowledge of OPW in the field of water pollution control, this article critically reviews and evaluates the technical feasibility of heterogeneous photocatalysis for OPW treatment, their bottlenecks in applications, and the way forward for the removal of recalcitrant hydrocarbon compounds from OPW. This work also presents the nature, composition, and health implications of these compounds in the OPW. Pertinent factors for effective photodegradation were presented. It also critically evaluates and discusses a variety of pilot and commercial-scale applications of photocatalysis in water treatment and its limitations. It was conclusively evident from 239 published articles (1988–2022) that heterogeneous photocatalytic degradation is a powerful approach for the removal of the hydrocarbon compounds such as PAHs, BTEX, and phenol with an average of over 80% of degradation efficiency. The photocatalytic process can be scaled up to the commercial scale with the proper design of photocatalytic reactors and the synthesis of advanced photocatalyst